Dangerous refuge - Lowell, Elizabeth, 1944- (William Morrow An Imprint of HarperCollinsPublishers, 2013)
Environmental conservancy advocate Shayne and big city cop Tanner join forces to uncover the truth behind Tanner's uncle's death. When Shaye becomes a killer's target, Tanner realizes he'd give up anything to protect her -- including his life.